Identifikasi, Keragaman dan Sebaran Satwa Mamalia di Suaka Margasatwa Lamandau, Kalimantan Tengah: Identification, Diversity and Distribution of Mammals in the Lamandau Wildlife Reserve, Central Kalimantan - Mubaraki, Ahmad; Wahyudi, Wahyudi; Fauzi, Fouad (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2023)
Lamandau Wildlife Reserve is a conservation area in Indonesia that protects various rare animals, especially orangutan mammals. This research aims to identify, analyze the diversity and distribution of mammals in the Lamandau Wildlife Reserve. The research was conducted at Tapak Resak in the north, Tapak Teringin in the east and Tapak Danau Burung in the west starting from May to October 2023 through direct and indirect observations using 28 camera traps. Data analysis is directed at identification, diversity, evenness, richness and distribution of mammal species. The research results showed that 11 camera traps succeeded in recording mammals consisting of 4 orders, 11 families and 15 species of mammals. Based on the calculation results, the diversity index is classified as medium, the evenness index is classified as high and the wealth index is classified as low. The mammals that have the highest distribution are sambar deer and mouse deer with native occupancy of 36%, monkeys and orangutans with native occupancy of 27%, bearded pigs, long-tailed monkeys, sun bears and yellow deer with native occupancy of 18% while the rock cat, garangan, white-headed civet, striped civet, tenggalung civet, three-colored squirrel and coconut squirrel with native occupancy of 9%.